Light valve, iodopyrazine and preparation method and application thereof
By preparing nanosheet-shaped iodopyrazine and applying it to the suspended particle layer of the light valve, the energy consumption problem caused by the need for continuous power on the existing SPD light valve is solved, and the trans-regulation of light transmittance is achieved, which promotes the SPD technology Development and application.
Patent Information
- Application Number
- CN202211558453.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-12-06
AI Technical Summary
The existing SPD light valves need to be continuously powered on when they remain transparent, resulting in high energy consumption. The research on nanosheets as trans-liquid light valves is limited, which limits the development and application of SPD technology.
By mixing nitrocellulose solution, elemental iodine and calcium iodide, stirring, adding 2,5-pyrazine dicarboxylic acid, methanol and water, ultrasonic treatment obtains iodine pyrazine in the form of nanosheets and applying it to the light valve In the suspended particle layer, trans-regulation of light transmittance is achieved.
It realizes trans-regulation of light transmittance of light valves, reduces energy consumption, conforms to environmental protection concepts and the laws of sustainable development, and broadens the types of SPD liquid light valves, promoting the development and application of SPD-type smart glass.
Smart Images

Figure CN115838357B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of light valves, and in particular to a light valve, iodopyrazine and a preparation method and application thereof. Background Art
[0002] At present, the world is facing the problem of resource shortage and energy waste, and activities such as heating, cooling, ventilation and lighting in residential and commercial buildings also consume a lot of energy. Therefore, in order to reduce energy consumption in life, it is necessary to design a new, intelligent and environmentally friendly material and technology. For example, smart windows with adjustable transmittance can reduce the transmittance of sunlight in hot weather and reduce the energy consumption of air conditioning equipment. It can also increase the transmittance in colder winters to improve lighting and heating. For these reasons, there is no doubt that smart windows with adjustable transmittance are more attractive than static windows currently used in most buildings. Among the various technologies exploring smart windows, suspended particle device (SPD) light valve technology has the advantages of high transmittance and fast response speed. At present, when an external electric field is applied to conventional SPD light valves, the particles are polarized and rotated under the torque applied by the electric field, and are aligned with the applied electric field, the light transmittance increases, and the glass becomes transparent. When the electric field is turned off, the direction of the particles becomes random in the medium, thereby blocking more photons and reducing the light transmittance. However, the demand for glass to remain transparent is longer and more frequent. The disadvantage of this SPD light valve is that it needs to be powered on continuously to keep the glass transparent for a long time, which causes a lot of energy consumption. The reverse SPD light valve is just the opposite. When it is not powered on, the glass can remain transparent; when the transparency needs to be reduced, the power needs to be turned on. This method can greatly reduce energy waste and conform to the concept of environmental protection and the law of sustainable development.
[0003] As described above, the light valve adjusts the light flux by flipping the particles inside it under an applied voltage. At present, there are very limited literature and scientific reports on nanosheets as trans-liquid light valves at home and abroad, which restricts the development and application of SPD technology. Therefore, the present invention is of great significance for broadening the types of SPD liquid light valves and promoting the further development and application of SPD-type smart glass. It is even more necessary to propose new materials with trans-adjustable light transmittance. Summary of the invention
[0004] The purpose of the present invention is to overcome the above technical deficiencies, provide a light valve, iodopyrazine and a preparation method and application thereof, and solve the problem of how to achieve trans-adjustable light transmittance in the prior art.
[0005] In order to achieve the above technical purpose, the technical solution of the present invention provides a method for preparing iodopyrazine, comprising the following steps:
[0006] A nitrocellulose solution, elemental iodine and calcium iodide are mixed to obtain a mixed solution, and then the mixed solution is stirred at 60-70° C., and then the mixed solution is cooled to 40-50° C., and 2,5-pyrazinedicarboxylic acid, methanol and water are added to the mixed solution and stirred to obtain the iodopyrazine.
[0007] Furthermore, after obtaining the iodopyrazine, the process further includes washing the iodopyrazine with isoamyl acetate; or, after adding 2,5-pyrazinedicarboxylic acid, methanol and water to the mixed solution and stirring, the process further includes ultrasonic treatment to obtain the iodopyrazine.
[0008] Furthermore, the solvent in the nitrocellulose solution is isoamyl acetate; or, the solvent in the nitrocellulose solution is a mixture of ethyl acetate and isoamyl acetate, and the mass ratio of the ethyl acetate to the isoamyl acetate is (8-9):(10-15).
[0009] Furthermore, in the nitrocellulose solution, nitrocellulose accounts for 1%-10% of the total solution volume.
[0010] Furthermore, the molar ratio of the elemental iodine to the calcium iodide is 1:(1-3); and / or, the material ratio of the elemental iodine to the nitrocellulose in the nitrocellulose solution is 1 mmol:(1-3) g; and / or, the molar ratio of the elemental iodine to the 2,5-pyrazinedicarboxylic acid is 1:(1-2); and / or, the material ratio of the elemental iodine to the methanol and the water is 1 mmol:(0.1-3) mL:(1-5) mL.
[0011] Further, the mixed solution is stirred at 60-70° C. for 30-60 min; and / or 2,5-pyrazinedicarboxylic acid, methanol and water are added to the mixed solution and stirred for 2-4 hours.
[0012] In addition, the present invention also provides iodopyrazine, which is prepared by the above preparation method.
[0013] Furthermore, the iodopyrazine has a nanosheet shape with a diameter of 1-2 μm and a thickness of less than 200 nm.
[0014] In addition, the present invention also proposes an application of the iodine pyrazine in manufacturing a light valve.
[0015] Furthermore, the present invention also proposes a light valve, comprising a first transparent electrode, a second transparent electrode and a suspended particle layer located between the first transparent electrode and the second transparent electrode; the suspended particle layer is obtained by mixing the above-mentioned iodine pyrazine and a suspension medium to obtain the suspension, and then injecting the suspension between the first transparent electrode and the second transparent electrode; preferably, the mass fraction of the iodine pyrazine in the suspension is 0.1-6%.
[0016] Compared with the prior art, the beneficial effects of the present invention include: the present invention mixes nitrocellulose solution, elemental iodine and calcium iodide to obtain a mixed solution, and then stirs the mixed solution at 60-70° C. The higher temperature is conducive to the combination of iodine and calcium iodide to form I 3 - ions, and then the mixture is cooled to 40-50° C., 2,5-pyrazinedicarboxylic acid, methanol and water are added to the mixture and stirred to obtain the iodopyrazine. Methanol and water can adjust the morphology and size of the product, and lower temperature is beneficial to the formation of I 3 - The ions are combined with pyrazine to obtain the target product, nanosheet-shaped iodopyrazine, which has a nanosheet-shaped morphology. The light transmittance of the light valve made of the iodopyrazine can be reversely adjusted. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic diagram of the structure of the light valve in a specific implementation manner of the present invention.
[0018] Figure 2 It is a scanning electron microscope image of iodopyrazine prepared in Example 1 of the present invention.
[0019] Figure 3 It is a scanning electron microscope image of iodopyrazine prepared in Example 2 of the present invention.
[0020] Figure 4 It is a scanning electron microscope image of iodopyrazine prepared in Comparative Example 1 of the present invention.
[0021] Figure 5 It is a scanning electron microscope image of iodopyrazine prepared in Comparative Example 2 of the present invention.
[0022] Figure 6 These are the test results of the first average light transmittance and the second average light transmittance of the light valve made of iodopyrazine in Example 1 of the present invention.
[0023] Figure 7 These are the test results of the first average light transmittance and the second average light transmittance of the light valve made of iodopyrazine according to Example 2 of the present invention.
[0024] Figure 8 These are the test results of the first average light transmittance and the second average light transmittance of the light valve made of iodopyrazine in Comparative Example 1 of the present invention.
[0025] Fig. 9 These are the test results of the first average light transmittance and the second average light transmittance of the light valve made of iodopyrazine in Comparative Example 2 of the present invention.
[0026] Explanation of the accompanying drawings: 1. first transparent electrode; 2. second transparent electrode; 3. suspended particle layer. DETAILED DESCRIPTION
[0027] This specific embodiment provides a method for preparing iodopyrazine, comprising the following steps:
[0028] A nitrocellulose solution, elemental iodine and calcium iodide are mixed to obtain a mixed solution, and then the mixed solution is stirred at 60-70° C. for 30-60 minutes, and then the mixed solution is cooled to 40-50° C., 2,5-pyrazinedicarboxylic acid, methanol and water are added to the mixed solution and stirred for 2-4 hours to obtain the iodopyrazine; the solvent in the nitrocellulose solution is isoamyl acetate; or the solvent in the nitrocellulose solution is a mixture of ethyl acetate and isoamyl acetate, and the mass ratio of ethyl acetate to isoamyl acetate is (8-9):(10-15); the nitrocellulose in the nitrocellulose solution accounts for 1% of the total solution volume -10%; the molar ratio of the elemental iodine to the calcium iodide is 1:(1-3); and / or the material ratio of the elemental iodine to the nitrocellulose in the nitrocellulose solution is 1mmol:(1-3)g; and / or the molar ratio of the elemental iodine to the 2,5-pyrazinedicarboxylic acid is 1:(1-2); and / or the material ratio of the elemental iodine to the methanol and the water is 1mmol:(0.1-3)mL:(1-5)mL, further, the 2,5-pyrazinedicarboxylic acid is one or both of anhydrous 2,5-pyrazinedicarboxylic acid and 2,5-pyrazinedicarboxylic acid dihydrate, and the calcium iodide is calcium iodide tetrahydrate.
[0029] In certain embodiments, after obtaining the iodopyrazine, the iodopyrazine reaction product is washed with isoamyl acetate for more than two times. Multiple washings with isoamyl acetate are beneficial to obtaining iodopyrazine nanosheets of suitable sizes. Alternatively, after adding 2,5-pyrazinedicarboxylic acid, methanol and water to the mixed solution and stirring, further ultrasonic treatment is performed to obtain the iodopyrazine. Ultrasonic treatment promotes the complete completion of the reaction.
[0030] In certain embodiments, after adding 2,5-pyrazinedicarboxylic acid, methanol and water to the mixed solution and stirring for 2-4 hours, ultrasonic treatment is further performed for 1-3 hours to promote the complete reaction to obtain the iodopyrazine.
[0031] This specific embodiment also proposes an iodine pyrazine, which is prepared by the above-mentioned preparation method. Furthermore, the iodine pyrazine has the morphology of nanosheets with a diameter of 1-2 μm and a thickness of less than 200 nm.
[0032] This specific implementation also proposes an application of the above-mentioned iodopyrazine in the manufacture of a light valve.
[0033] In addition, combined Figure 1This specific embodiment also proposes a light valve, comprising a first transparent electrode 1, a second transparent electrode 2, and a suspended particle layer 3 located between the first transparent electrode 1 and the second transparent electrode 2; the suspended particle layer 3 is obtained by mixing the above-mentioned iodine pyrazine and a suspension medium to obtain the suspension, and then injecting the suspension between the first transparent electrode and the second transparent electrode; preferably, the mass fraction of the iodine pyrazine in the suspension is 0.1-6%. Further, the first transparent electrode 1 or the second transparent electrode 2 includes but is not limited to ITO conductive glass, ITO conductive film, nano Ag wire conductive film, nano Cu wire conductive film, PEDOT conductive film, graphene conductive film, carbon nanotube conductive film, etc.
[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0035] Example 1
[0036] This embodiment provides an iodopyrazine, which is prepared by the following steps:
[0037] 4 g of 1 / 4 second viscosity nitrocellulose was dissolved in 36 g of isoamyl acetate to prepare a 10% nitrocellulose solution; 1.5 mmol of elemental iodine and 1.5 mmol of calcium iodide tetrahydrate were added to the nitrocellulose solution to obtain a mixed solution, the mixed solution was transferred to a two-necked flask, the mixed solution was heated to 65°C and stirred for 40 minutes; then the mixed solution was cooled to 45°C, 2 mmol of anhydrous 2,5-pyrazine dicarboxylic acid was added, 0.9 ml of methanol and 1 ml of deionized water were added after stirring evenly; then the mixed solution was stirred for 3 hours, and ultrasonic reaction was continued for 2 hours to obtain iodopyrazine nanosheets; after the reaction, the reaction product was washed with isoamyl acetate and centrifuged twice to obtain iodopyrazine, from Figure 2 It can be seen that the iodopyrazine is a nanosheet with a diameter of 1-2 μm and a thickness of less than 200 nm.
[0038] Example 2
[0039] This embodiment provides an iodopyrazine, which is prepared by the following steps:
[0040] 12g of ethyl acetate solution containing 14% nitrocellulose was mixed with 24g of isoamyl acetate to prepare a mixed solution; 1.5mmol of elemental iodine and 3mmol of calcium iodide tetrahydrate were added to the mixed solution, and the mixed solution was transferred to a two-necked flask, and then the mixed solution was heated to 65°C and stirred for 40min; then the mixed solution was cooled to 45°C, 2mmol of 2,5-pyrazinedicarboxylic acid dihydrate was added, and after stirring evenly, 1ml of methanol and 3ml of deionized water were added; then the mixed solution was stirred for 3 hours, ultrasonic reaction was continued for 2h, and iodine pyrazine nanosheets were obtained by centrifugation; after the reaction, the reaction product was washed with isoamyl acetate and centrifuged 3 times to obtain iodine pyrazine, from Figure 3 It can be seen that the iodopyrazine is a nanosheet with a diameter of 1-2 μm and a thickness of less than 200 nm.
[0041] Example 3
[0042] This embodiment provides an iodopyrazine, which is prepared by the following steps:
[0043] 10g of ethyl acetate solution containing 15% nitrocellulose was mixed with 20g of isoamyl acetate to prepare a mixed solution; 1.5mmol of elemental iodine and 4.5mmol of calcium iodide tetrahydrate were added to the mixed solution, and the mixed solution was transferred to a two-necked flask, and then the mixed solution was heated to 70°C and stirred for 60min; then the mixed solution was cooled to 40°C, 3mmol of 2,5-pyrazinedicarboxylic acid dihydrate was added, and after stirring evenly, 0.06ml of methanol and 7.5ml of deionized water were added; then the mixed solution was stirred for 2 hours, ultrasonic reaction was continued for 1h, and iodine pyrazine nanosheets were obtained by centrifugation; after the reaction, the reaction product was washed with isoamyl acetate and centrifuged 3 times to obtain iodine pyrazine nanosheets.
[0044] Example 4
[0045] This embodiment provides an iodopyrazine, which is prepared by the following steps:
[0046] 20g of ethyl acetate solution containing 14% nitrocellulose was mixed with 30g of isoamyl acetate to prepare a mixed solution; 1.5mmol of elemental iodine and 1.5mmol of calcium iodide tetrahydrate were added to the mixed solution, and the mixed solution was transferred to a two-necked flask, and then the mixed solution was heated to 60°C and stirred for 30min; then the mixed solution was cooled to 50°C, 1.5mmol of 2,5-pyrazinedicarboxylic acid dihydrate was added, and after stirring evenly, 4.5ml of methanol and 1.5ml of deionized water were added; then the mixed solution was stirred for 4 hours, ultrasonic reaction was continued for 3h, and iodine pyrazine nanosheets were obtained by centrifugation; after the reaction, the reaction product was washed with isoamyl acetate and centrifuged 3 times to obtain iodine pyrazine nanosheets.
[0047] Comparative Example 1
[0048] The difference between this comparative example and Example 1 is that 36 g of ethyl acetate is used instead of isoamyl acetate. The other reaction conditions are the same as those in Example 1. No nano-sheet iodine pyrazine is obtained. The morphology of iodine pyrazine is as follows: Figure 4 As shown, it is in the form of irregular large particles.
[0049] Comparative Example 2
[0050] The difference between this comparative example and Example 1 is that no deionized water is added, and the other reaction conditions are the same as those in Example 1. No nano-sheet iodine pyrazine is obtained. The morphology of iodine pyrazine is as follows: Figure 5 As shown, it is in the shape of a short rod.
[0051] Example 5
[0052] Making the light valve:
[0053] 24.4 g of lauryl methacrylate, 0.6 g of hydroxypropyl methacrylate and 30 g of toluene were uniformly mixed in a two-necked flask, and 2 g of hexanethiol was added to the resulting mixture;
[0054] 10 g of toluene solution containing 0.2 g of azobisisobutyl cyanide was uniformly mixed with the above organic mixture and heated to 40 °C. 2 Under protection, the polymerization reaction was carried out at 60° C. for 18 hours to obtain a suspension medium with a viscosity of about 1600 cp; it should be noted that, in other embodiments, the suspension medium includes but is not limited to siloxane, acrylic acid, and alkylene oxide monomers or polymers, preferably, the suspension medium is an acrylic polymer;
[0055] The iodopyrazine of Example 1-4 and Comparative Example 1-2 was mixed in a suspension medium at a mass fraction of 5% by ultrasonic and stirring to obtain a suspension;
[0056] Insert a 200μm thick PVC transparent frame between two pieces of ITO conductive glass and fix them with insulating glue;
[0057] Take an appropriate amount of suspension, use a syringe to fill the space between two layers of ITO conductive glass, and use insulating glue to encapsulate to obtain a simple SPD light valve. The structure of the simple SPD light valve is as follows: Figure 1 As shown, the light valve comprises a first transparent electrode 1 and a second transparent electrode 2 and a suspended particle layer 3 located therebetween. The first average transmittance of the light valve to light in the wavelength range of 280-780nm was tested in the "OFF" state (indicating no power was supplied), and the second average transmittance of the light valve to light was tested in the "ON" state (indicating power was supplied) after applying a voltage of 120V. The results are shown in Table 1. Figure 6-9The test results of the first average light transmittance and the second average light transmittance of the light valves made of iodopyrazine in Example 1-2 and Comparative Example 1-2 are shown respectively.
[0058] Table 1 The first average light transmittance and the second average light transmittance of the light valves made in Examples 1-4 and Comparative Examples 1-2 measured
[0059]
[0060] Combination Figure 6-9 As can be seen from Table 1, after the light valves made of iodine pyrazine in Examples 1-4 were powered on, the second average transmittance decreased, achieving a reverse regulation of the transmittance, and the first average transmittance and the second average transmittance of Examples 2-4 were smaller than those of Example 1, especially the second average transmittance of Example 2 could be as low as 4.87%, while the average transmittance of Example 1 before and after power-on was almost unchanged, while the second average transmittance of Example 2 was slightly higher than the first average transmittance, indicating that a positive regulation of the transmittance occurred, indicating that the morphology greatly affected the average transmittance of iodine pyrazine before and after power-on.
[0061] The present invention adopts a solvothermal method to prepare iodine pyrazine nanosheets for the first time and applies them to a reverse SPD light valve. When a voltage is applied to the device, the transmittance of the incident light can be reversely adjusted.
[0062] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing iodopyrazine nanosheets, characterized in that: The following steps are involved: A nitrocellulose solution, elemental iodine and calcium iodide are mixed to obtain a mixed solution, and then the mixed solution is stirred at 60-70° C., and then the mixed solution is cooled to 40-50° C., 2,5-pyrazinedicarboxylic acid, methanol and water are added to the mixed solution, stirred, and ultrasonically treated to obtain the iodine pyrazine nanosheets, and then the iodine pyrazine nanosheets are washed with isoamyl acetate; The molar ratio of the elemental iodine to the calcium iodide is 1:(1-3); the material ratio of the elemental iodine to the nitrocellulose in the nitrocellulose solution is 1mmol:(1-3)g; the molar ratio of the elemental iodine to the 2,5-pyrazinedicarboxylic acid is 1:(1-2); the material ratio of the elemental iodine to the methanol and the water is 1mmol:(0.1-3)mL:(1-5)mL; The solvent in the nitrocellulose solution is isoamyl acetate; or, the solvent in the nitrocellulose solution is a mixture of ethyl acetate and isoamyl acetate, and the mass ratio of the ethyl acetate to the isoamyl acetate is (8-9):(10-15); In the nitrocellulose solution, nitrocellulose accounts for 1%-10% of the total solution volume.
2. The method for preparing iodopyrazine nanosheets according to claim 1, characterized in that: The mixed solution is stirred at 60-70° C. for 30-60 minutes; and / or 2,5-pyrazinedicarboxylic acid, methanol and water are added to the mixed solution and stirred for 2-4 hours.
3. An iodopyrazine nanosheet, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 2.
4. The iodopyrazine nanosheet according to claim 3, characterized in that: The diameter is 1-2μm and the thickness is less than 200 nm.
5. Use of the iodopyrazine nanosheets according to any one of claims 3 to 4 in the manufacture of light valves.
6. A light valve, characterized in that: It comprises a first transparent electrode, a second transparent electrode and a suspended particle layer located between the first transparent electrode and the second transparent electrode; the suspended particle layer is obtained by mixing the iodopyrazine nanosheets described in any one of claims 3 to 4 with a suspension medium to obtain the suspension, and then injecting the suspension between the first transparent electrode and the second transparent electrode.
7. The light valve according to claim 6, characterized in that: The mass fraction of the iodine pyrazine nanosheets in the suspension is 0.1-6%.
Citation Information
Patent Citations
Light valve device containing nonlinear structure liquid polymer, nonlinear structure liquid polymer and preparation method of nonlinear structure liquid polymer
CN113917757A
Dispersant, method for producing polarizing particle, dispersed resin composition, curable composition and film for suspended particle device
JP2010126624A